Influence of the Molar Activity of 203/212Pb-PSC-PEG2-TOC on Somatostatin Receptor Type 2-Binding and Cell Uptake - Marc Pretze; Enrico Michler; Roswitha Runge; Kerstin Wetzig; Katja Tietze; Florian Brandt; Michael K. Schultz; Jörg Kotzerke (MDPI AG, 2023)
(1) Background: In neuroendocrine tumors (NETs), somatostatin receptor subtype 2 is highly expressed, which can be targeted by a radioactive ligand such as [177Lu]Lu-1,4,7,10-tetraazacyclododecane-N,N',N",N‴,-tetraacetic acid-[Tyr3,Thr8]-octreotide (177Lu-DOTA-TOC) and, more recently, by a lead specific chelator (PSC) containing 203/212Pb-PSC-PEG2-TOC (PSC-TOC). The molar activity (AM) can play a crucial role in tumor uptake, especially in receptor-mediated uptake, such as in NETs. Therefore, an investigation of the influence of different molar activities of 203/212Pb-PSC-TOC on cell uptake was investigated. (2) Methods: Optimized radiolabeling of 203/212Pb-PSC-TOC was performed with 50 µg of precursor in a NaAc/AcOH buffer at pH 5.3-5.5 within 15-45 min at 95° C. Cell uptake was studied in AR42 J, HEK293 sst2, and ZR75-1 cells. (3) Results: 203/212Pb-PSC-TOC was radiolabeled with high radiochemical purity >95% and high radiochemical yield >95%, with AM ranging from 0.2 to 61.6 MBq/nmol. The cell uptake of 203Pb-PSC-TOC (AM = 38 MBq/nmol) was highest in AR42 J (17.9%), moderate in HEK293 sstr (9.1%) and lowest in ZR75-1 (0.6%). Cell uptake increased with the level of AM. (4) Conclusions: A moderate AM of 15-40 MBq/nmol showed the highest cell uptake. No uptake limitation was found in the first 24-48 h. Further escalation experiments with even higher AM should be performed in the future. It was shown that AM plays an important role because of its direct dependence on the cellular uptake levels, possibly due to less receptor saturation with non-radioactive ligands at higher AM.